Nitric oxide synthase inhibition with l-NAME reduces maximal oxygen uptake but not gas exchange threshold during incremental cycle exercise in man - Jones, Andrew M (Blackwell Science Inc, 2004)
We hypothesized that the effective inhibition of nitric oxide synthase (NOS), achieved via systemic infusion of N(G)-nitro-l-arginine methyl ester (l-NAME), would reduce the gas exchange threshold (GET) and the maximal oxygen uptake (V˙(O(2))(max)) during incremental cycle exercise in man if NO is important in the regulation of muscle vasodilatation. Seven healthy males, aged 18–34 years, volunteered to participate in this ethically approved study. On two occasions, the subjects completed an incremental exercise test to exhaustion on an electrically braked cycle ergometer following the infusion of either l-NAME (4 mg kg(−1) in 50 ml saline) or placebo (50 ml saline, CON). At rest, the infusion of l-NAME resulted in a significant increase in mean arterial pressure (MAP; CON vs. l-NAME, 89 ± 8 vs. 103 ± 11 mmHg (mean ± s.d.; P < 0.05)) and a significant reduction in heart rate (HR; CON vs. l-NAME, 60 ± 12 vs. 51 ± 8 beats min(−1); P < 0.01). At submaximal work rates, there was no significant difference in V˙(O(2)) between the conditions and no difference in the GET (CON vs. l-NAME, 1.94 ± 0.47 vs. 2.01 ± 0.41 l min(−1)). However, at higher work rates, differences in V˙(O(2)) between the conditions became more pronounced such that V˙(O(2))(max) was significantly lower with l-NAME (CON vs. l-NAME, 4.02 ± 0.41 vs. 3.80 ± 0.34 l min(−1); P < 0.05). The reduction in V˙(O(2))(max) was associated with a reduction in HR(max) (CON vs. l-NAME, 186 ± 10 vs. 178 ± 7 beats min(−1); P < 0.01). These results demonstrate that NOS inhibition with l-NAME has no effect on GET but reduces V˙(O(2))(max) during large muscle group exercise in man, presumably by direct or indirect effects on cardiac output and muscle blood flow.